Adult‐onset BRAF V600E‐related multisystem Langerhans cell histiocytosis treated with vemurafenib - Lisa Denise A. Encarnacion‐Mangubat; Lonabel A. Encarnacion (Wiley, 2024)
Abstract We report a case of a 65‐year‐old female with 1‐year history of dental pain and oral ulcers. A diagnosis of Langerhans cell histiocytosis (LCH) was made by oral biopsy and CD207 (Langerin) stain, and BRAF V600E mutation was identified. PET/CT revealed an enhancing lesion in the hard palate with extension into the maxillary sinus. Chemotherapy with cytarabine failed, and LCH progressed to affect additional organ systems. Treatment with vemurafenib was started, resulting in a dramatic improvement of painful mucocutaneous ulcers since the first month of treatment. Vemurafenib is effective in children with refractory BRAF V600E‐mutated LCH, and recent data support the use of vemurafenib in adults with refractory multisystem LCH harbouring the same mutation.